2021
DOI: 10.3390/plants10112261
|View full text |Cite
|
Sign up to set email alerts
|

Light Deficiency Inhibits Growth by Affecting Photosynthesis Efficiency as well as JA and Ethylene Signaling in Endangered Plant Magnolia sinostellata

Abstract: The endangered plant Magnolia sinostellata largely grows in the understory of forest and suffers light deficiency stress. It is generally recognized that the interaction between plant development and growth environment is intricate; however, the underlying molecular regulatory pathways by which light deficiency induced growth inhibition remain obscure. To understand the physiological and molecular mechanisms of plant response to shading caused light deficiency, we performed photosynthesis efficiency analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 112 publications
(145 reference statements)
2
10
0
Order By: Relevance
“…In the experiment with temporary light deprivation, no significant effects of different water conditions were recorded, which suggests that the dark stress affected traits associated with spike fertility and contributed to the limitation of drought effects on spike morphology. Like several previous studies [69,70] demonstrating the negative impact of light distortion on the vegetative and generative cycle of plant development and other different aspects of plant biology [71,72], the present study also revealed that temporary light deficiency is a stronger stressor for seed development than drought occurrence. Interestingly, the drought conditionapplied in both Exp 1 and Exp 2 -contributed positively to FSm with increased values recorded for CamB.…”
Section: Spike Fertility and Anther Morphologysupporting
confidence: 86%
“…In the experiment with temporary light deprivation, no significant effects of different water conditions were recorded, which suggests that the dark stress affected traits associated with spike fertility and contributed to the limitation of drought effects on spike morphology. Like several previous studies [69,70] demonstrating the negative impact of light distortion on the vegetative and generative cycle of plant development and other different aspects of plant biology [71,72], the present study also revealed that temporary light deficiency is a stronger stressor for seed development than drought occurrence. Interestingly, the drought conditionapplied in both Exp 1 and Exp 2 -contributed positively to FSm with increased values recorded for CamB.…”
Section: Spike Fertility and Anther Morphologysupporting
confidence: 86%
“…S1). Moreover, the net photosynthetic rate (Pn) and photochemical efficiency (Fv/Fm) declined obviously during the treatment, indicating that photosynthesis ability of M. sinostellata impaired 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Leaves and seedlings of M. sinostellta gradually wilt under light deficiency treatment, and severe leaf abscission was observed, which was distinct from low light responses of module plants such as Arabidopsis 48 and rice 46 . Photosynthesis is essential for plant growth and development, and key photosynthetic indicators Pn and Fv/Fm were both decreased significantly in M. sinostellta 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Leaf expansion was restricted in Glycine max and Zea mays growing in the shade, which had an impact on seed yield [45]. In the case of vegetable crops such as tomato, cucumber, and eggplant, seedlings often develop abnormally under low light circumstances, resulting in lower yields in the field [17]. Phytochromes (PHY), which sense changes in both light intensity and quality, can sense changes in the light under canopy shade [46].…”
Section: Light Stress Consequencesmentioning
confidence: 99%